2007
DOI: 10.1016/j.jfluchem.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluoro-, heptafluoro-, and octafluoro-salts, and [MnF5n+1]− (n=2, 3, 4) polyfluorometallates of singly charged metal cations, Li+–Cs+, Cu+, Ag+, In+ and Tl+

Abstract: ReviewHexafluoro-, heptafluoro-, and octafluoro-salts, and [M n F 5n+1 ] À (n = 2, 3, 4) polyfluorometallates of singly charged metal cations,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…The majority of AMF 6 compounds whose A + cations have radii larger than 1.5 Å crystallize in the KOsF 6 structure type (during this study it has been confirmed that this is valid also for [CrF 6 ] -salts of K, Rb and Cs). [29] The reported elemental chemical analysis of their product also gave a low value for the fluorine content and a high value for the chromium content. [9] Our attempts to prepare pure CsCrF 6 and other ACrF 6 (A = Li, Na, K, and Rb) compounds by reactions between the corresponding metal fluoride and CrF 5 at 333 K in reaction vessels made from more inert materials (perfluorinated polymers) than fussed silica failed.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The majority of AMF 6 compounds whose A + cations have radii larger than 1.5 Å crystallize in the KOsF 6 structure type (during this study it has been confirmed that this is valid also for [CrF 6 ] -salts of K, Rb and Cs). [29] The reported elemental chemical analysis of their product also gave a low value for the fluorine content and a high value for the chromium content. [9] Our attempts to prepare pure CsCrF 6 and other ACrF 6 (A = Li, Na, K, and Rb) compounds by reactions between the corresponding metal fluoride and CrF 5 at 333 K in reaction vessels made from more inert materials (perfluorinated polymers) than fussed silica failed.…”
Section: Resultsmentioning
confidence: 97%
“…In the regular [CrF 6 ] -octahedra, the six Cr-F distances are 1.722(5) Å. The orthorhombic crystal structure of NaCrF 6 (phase-I) is not related to other AMF 6 structures [29] and appears to be a new type of structure. It consists of Na + cations and highly distorted [CrF 6 ] -octahedra ( Figure 3, Table 2) with Cr-F bond lengths in the range 1.6939(19)-1.8046(13) Å (Table 1).…”
Section: X-ray Crystal Structures Of Acrfmentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous work, radii of ions in OIPCs were estimated by the hard sphere model. 28 In this procedure, the radius of PF 6 ¹ was first calculated from disordered inorganic salts, 32,33 6 ] system forms solid solution with the NaCl-type structure at any mixing ratio. This difference suggests that the substitution of the smaller constituent ion (anion in this case) in solid solution is easier than that of the larger constituent ion (cation in this case).…”
Section: Electrochemistry (In Press)mentioning
confidence: 99%
“…While structure and properties of crystalline complex fluorotantalates are in many cases known, (recently comprehensive review of fluorometalates including fluorotantalates has been published [10]), the understanding of the ionic structure of melts is still in development. According to Agulyansky [1,6] three conceptual steps can be discerned in definition of the ionic structure of fluoride melts containing tantalum.…”
Section: Introductionmentioning
confidence: 99%